Actions Taken by Public Companies in Favor of Corporate Social Responsibility – A Polish Case - Anna MATUSZEWSKA (Communications of International Proceedings, 2020)
In the publication by Bowen called Social Responsibilities of the Businessman, which became the first complex discussion about business ethics and social responsibility, a need to run a company taking into account needs of a given company’s surroundings, was mentioned for the first time. [Bowen 1953]. According to the concept of corporate social responsibility, an entrepreneur who functions in a certain social and natural environment, cannot disregard its needs and interests. As Bowen notices, decisions made by entrepreneurs have a direct influence on the life of people in a society. The main aim of this article is to give an answer to the question if endeavours made by public companies fall into the category of corporate social responsibility. The more detailed aim is an endeavour to answer the question if taking this type of actions is treated like a sense of responsibility or a need? The article concentrates on giving an overview of critical activities of a selected company in recent years paying special attention to the period of COVID 19 epidemic. In order to achieve the aforementioned goal, a thorough analysis of special literature was carried out as well as unstandardized techniques of direct interviewing were applied. In addition to the above, both monographic method and the method of studying source documents were used in the article.
Keywords: Corporate Social Responsibility; Quality Management; Prosocial Actions; Ecology; The Health Of The Local Community; COVID 19.